2016
DOI: 10.18632/oncotarget.11621
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and circulating biomarkers in patients with second-line hepatocellular carcinoma from the randomized phase II study with tivantinib

Abstract: ARQ 197-215 was a randomized placebo-controlled phase II study testing the MET inhibitor tivantinib in second-line hepatocellular carcinoma (HCC) patients. It identified tumor MET as a key biomarker in HCC.Aim of this research was to study the prognostic and predictive value of tumor (MET, the receptor tyrosine kinase encoded by the homonymous MNNG-HOS transforming gene) and circulating (MET, hepatocyte growth factor [HGF], alpha-fetoprotein [AFP], vascular endothelial growth factor [VEGF]) biomarkers in secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
3
58
0
2
Order By: Relevance
“…Despite this clinical need, a lack of progress in this field occurred due to the scarcity of HCC tissues, particularly those obtained at advanced stages and before sorafenib treatment. In a recent analysis, MET (the receptor tyrosine kinase encoded by the homonymous MNNG-HOS transforming gene) showed a significantly higher expression after than before sorafenib treatment [27]. This is in line with literature suggesting that high MET expression correlates with hypoxia, resistance to anti-angiogenic therapies, and poor prognosis in HCC, and further supports the prognostic role of MET.…”
Section: Tissue Markerssupporting
confidence: 74%
“…Despite this clinical need, a lack of progress in this field occurred due to the scarcity of HCC tissues, particularly those obtained at advanced stages and before sorafenib treatment. In a recent analysis, MET (the receptor tyrosine kinase encoded by the homonymous MNNG-HOS transforming gene) showed a significantly higher expression after than before sorafenib treatment [27]. This is in line with literature suggesting that high MET expression correlates with hypoxia, resistance to anti-angiogenic therapies, and poor prognosis in HCC, and further supports the prognostic role of MET.…”
Section: Tissue Markerssupporting
confidence: 74%
“…A more recent study that specifically evaluated MET, HGF and AFP as circulating biomarkers (by 75 percentile) found that they were prognostic markers for overall survival in patients with HCC 57. Circulating MET was also a pharmacodynamic biomarker for tivantinib: patients on treatment with a ≥10% decrease in circulating MET levels demonstrated increased overall survival compared to those with a <10% decrease (13.3 months vs. 6.3 months; HR: 0.46 [95% CI: 0.24–0.86], p =0.01).…”
Section: Future Directionsmentioning
confidence: 99%
“…Therefore, refined patient selection by biomarkers (e.g., genetic abnormalities and expressed proteins) was recently proposed [55] . For example, c-MET overexpression was used as a biomarker in trials of tivantinib [46][47][48] , and RAS was used as a biomarker in a trial of an MEK inhibitor [56] . A trial of an FGFR inhibitor using FGF19 as a biomarker is currently ongoing.…”
Section: Major Difficulties Associated With Clinical Trials Of Molecumentioning
confidence: 99%
“…This agent selectively inhibits the hepatocyte growth factor receptor c-MET; strong expression of c-MET in liver cancer tissues is associated with poor prognosis. Following a phase II study that showed significant improvements in OS and TTP among patients with c-MET overexpression who received tivantinib [46,47] , a placebo-controlled phase III study was conducted on patients overexpressing c-MET in liver cancer tissues; this was the first biomarker-selected clinical trial for HCC. To reflect ethnic differences in metabolizing enzyme activities, studies with fundamentally the same design were separately carried out globally (METIV-HCC) and in Japan (JET-HCC) ( Table 1 ).…”
mentioning
confidence: 99%